PENGARUH EMOTIONAL INTELLIGENCE DAN KOMITMEN ORGANISASI TERHADAP KINERJA PERAWAT DENGAN ORGANIZATIONAL CITIZENSHIP BEHAVIOR SEBAGAI VARIABEL MEDIASI STUDI PADA PERAWAT RSUD dr. RASIDIN KOTA PADANG - Dinda Diah Pasya; Hendra Lukito; Harif Amali Rivai (Journal Publicuho, 2025)
The objective of this research is to examine the influence of Emotional Intelligence and Organisational Commitment on Employee Performance, with Organisational Citizenship Behaviour (OCB) acting as a mediating variable, among nurses at RSUD dr. Rasidin, Padang. This study applies a quantitative research design with a survey method. Data were collected from 160 respondents through questionnaires and analysed using Partial Least Squares-Structural Equation Modelling (PLS-SEM) with SmartPLS software. The empirical results indicate that Emotional Intelligence has a positive and significant effect on both OCB and Employee Performance. Similarly, Organisational Commitment demonstrates a positive and significant impact on OCB as well as Employee Performance. Furthermore, OCB shows a positive and significant contribution to Employee Performance and mediates the relationship between Emotional Intelligence, Organisational Commitment, and Employee Performance. These findings highlight the strategic role of OCB in strengthening the effect of Emotional Intelligence and Organisational Commitment on performance outcomes. The study contributes both theoretically and practically by emphasising the importance of emotional and organisational factors in enhancing extra-role behaviour, which ultimately improves employee performance in the healthcare sector.